(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
The aim of this research is to show the sudden critical position taken by Martin Heidegger on the philosophy of Friedrich Nietzsche, which was regarded by him as the last major metaphysical attempt in the history of Western philosophy. In fact, this view contradicts the Nietzschean philosophical texts; Nietzsche had a critical influence in confronting the metaphysical thinking itself. Therefore, Heidegger’s critique of Nietzsche lacks justification for releasing such critical judgments. Thus, Nietzsche’s real positions had to be demonstrated to find the appropriate methodology to achieve an objective perspective on this problem.